A formação do professor-supervisor de terapias psicodinâmicas: um estudo de educação médica - Barbosa, Mirian Haubold (2006)
The present study follows the Knowledge Formation and Professional Development research line, and aims to describe and understand the formation of the analytic psychotherapy supervisor. The qualitative method is used to increase the reflection on this formative process. The investigation had as subjects four psychoanalysts of the same generation, who works as professors and also as supervisors. The material was collected by means of semi-structured interviews, submitted to content analysis and then organized in four evaluation dimensions: personal, formative as supervisee, formative as supervisor and the formative process itself. Through the analysis of these dimensions the conclusion is that the formation of the professor-supervisor occurs in an empiric form, complementary to the specific formation of the psychotherapist, in a relation theory/person/professional identity. The professor-supervisor formation process is anchored in the supervision, through a cognitiveoaffective nature relation, which establishes an intersubjective communication between supervisor and supervisee, concomitant to the supervision dynamics and inside it. This interaction creates identification mechanisms that results in a professor professional identity based on the therapist professional identity, as a continuous process, subject to transformation during work activity.